Hand hygiene compliance among paediatric nurses in Ebonyi, Nigeria: a mixed methods study - Chioma, Oko Constance (2022)
Paediatric patients are more vulnerable to Hospital-Acquired Infections (HAIs). Hand Hygiene Compliance (HHC) is considered a cost-effective way of preventing HAIs. Compliance with this practice is not often assessed in Nigeria and thus poses a significance risk to the quality of care and patient safety, especially during COVID-19. The purpose of this study was to determine the level of HHC and explore factors that influence compliance among paediatric in paediatric care setting in Ebonyi State, Nigeria. A mixed-method research design was conducted in two phases: phase 1a and 1b comprises data collection using the WHO hand hygiene (HH) observational tool on the nurse’s perceived HHC and direct observation of their HHC practice. Phase 2 involved an in-depth interview exploring factors influencing compliance using a semistructured interview guide. The Statistical Package for Social Sciences (v26) was used to analyze the quantitative data while the qualitative data were analyzed thematically. Data collection commenced from the 26th of October 2020 to the 5th of March 2021. In phase 1a, 96 participants were involved in the survey, and all duty nurses on duty on the observation days were observed for HHC giving a total of 1417 HH opportunities in phase 1b. Phase 2 involved 17 staff nurses and five ward managers. Chi-square analysis showed that perceived compliance was significantly associated with HH education and last HH education (p<0.001). Chi-square tests revealed that the observed HH compliance varied significantly with the units, type of shift, and the five moments of HH (FMHH) (p<0.005). The perceived HHC rate was high compared to the observed compliance rate. The analysis of qualitative data was to identify organizational and contextual barriers and facilitators to HHC. Four key themes emerged from organizational factors: leadership, administrative responsibility, prompt, and HH monitoring. Three themes emerged from the contextual factor: experience, workload, and perception. This study showed that observed HHC among nurses in paediatric settings was poor. These challenges in this setup contributed to the poor compliance seen in this study. In designing HH intervention programs, a moment-by-moment approach should be employed to increase recall across all the moments. The findings of this study revealed the need for specific strategies such as training and retraining of nurses, improvement in HH facilities, and continuous HH monitoring with feedback on performance, especially during the COVID-19 pandemic. These measures will prevent HAIs among this vulnerable population as well as improve patient safety and quality of care.